2019
DOI: 10.17220/mojet.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ use of Web 2.0: Education Bag Project Experiences

Abstract: The main purpose of this research is to determine teachers' views on using Web 2.0 tools in education In accordance with this purpose, participant teachers were asked to express their expectations for the training before they took the training and perceptions on the training after completing it. Additionally, teachers were asked which Web 2.0 tools they liked the most. Within the scope of the project entitled "Education Bag: The Use of Web 2.0 Tools in Education" the research where teachers' views about the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
“…When the learners have completed one round of the game, they are able to review the questions and do revision on their own. This eventually leads them to remember the lesson content better, and therefore proves that Quizizz is effective in the teaching and learning of the English language [14,17,18,22,34]. An example of the effectiveness of Quizizz can be seen in the research carried out by Grabinski et al [23], where they used Quizizz as an intervention in the English language classroom.…”
Section: Teachers' Perspective On the Effectiveness Of Quizizzmentioning
confidence: 94%
See 2 more Smart Citations
“…Singh and Chan (2014) evidenced that although the majority of the teachers in their study demonstrated positive manners towards using technology as a tool for instruction, "they need intensive training in using information technology to facilitate its integration into classroom activities to enhance thinking and creativity". Likewise, Kurt, Sarsar, Filiz, Telli, Orhan-Göksün, and Bardakcı (2019) found that training teachers on the use of Web 2 toolshada positive contribution to their professional development and increased their self-confidence to use these tools in their teaching environments.As Phan and Dang (2017) stated,technical proficiencies strongly influence teacher e-readiness; therefore, to increase teacher ereadiness, training programs should be organized.…”
Section: Introductionmentioning
confidence: 96%